Keeping Faith at Princeton A Brief History of Religious Pluralism at Princeton and Other Universities. - Borsch, Frederick Houk. (Princeton : Princeton University Press, 2012)
In 1981, Frederick Houk Borsch returned to Princeton University, his alma mater, to serve as dean of the chapel at the Ivy League school. In Keeping Faith at Princeton, Borsch tells the story of Princeton's journey from its founding in 1746 as a college for Presbyterian ministers to the religiously diverse institution it is today. He sets this landmark narrative history against the backdrop of his own quest for spiritual illumination, first as a student at Princeton in the 1950s and later as campus minister amid the turmoil and uncertainty of 1980s America. Borsch traces how the trauma of the.
Cover; Contents; Introduction; ONE: The Protestant Heritage; TWO: Opportunity and Challenge; THREE: Religions at Princeton: The 1980s; FOUR: Religion and Religions at Other Universities; FIVE: Religions at Princeton Today; Acknowledgments; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; Y; Z
Description based upon print version of record.
Keywords: Princeton University - Religion - History; Religious pluralism - New Jersey - Princeton - History; Religious pluralism - United States - History; Universities and colleges - United States - Religion - History; Religion; Princeton University -- Religion -- History; Religious pluralism -- New Jersey -- Princeton -- History; Universities and colleges -- United States -- Religion -- History; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; Electronic books